2020
DOI: 10.1111/cobi.13567
|View full text |Cite
|
Sign up to set email alerts
|

Bird‐friendly wine country through diversified vineyards

Abstract: Vinecology, the integration of ecological and viticultural practices, focuses on the working landscapes of the Mediterranean‐climate biomes to make wine‐grape production compatible with species conservation. We examined how maintaining remnant native vegetation and surrounding natural areas in and around vineyards, two primary practices of vinecology, may influence bird community richness and composition across a vineyard landscape. We conducted bird surveys over spring and summer (October–January) at 120 site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 56 publications
(112 reference statements)
1
8
0
Order By: Relevance
“…Interestingly, we found that both configurational and compositional landscape heterogeneity were important for the conservation of functionally diverse bird communities in vineyards, as predicted by ecological theory (Fahrig et al, 2011). Such positive responses to heterogeneity are due to higher spatial complexity in mosaic landscapes, enhancing positive edge effects on insectivorous birds and their functional diversity, and allowing more complementation processes and spill-over movements between vineyards and adjacent semi-natural habitats (Barbaro et al, 2017;Muñoz-Sáez et al, 2020). Overall, landscape heterogeneity had a positive effect on taxonomic diversity and allowed the coexistence of multiple avian functions in vineyard landscapes.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Interestingly, we found that both configurational and compositional landscape heterogeneity were important for the conservation of functionally diverse bird communities in vineyards, as predicted by ecological theory (Fahrig et al, 2011). Such positive responses to heterogeneity are due to higher spatial complexity in mosaic landscapes, enhancing positive edge effects on insectivorous birds and their functional diversity, and allowing more complementation processes and spill-over movements between vineyards and adjacent semi-natural habitats (Barbaro et al, 2017;Muñoz-Sáez et al, 2020). Overall, landscape heterogeneity had a positive effect on taxonomic diversity and allowed the coexistence of multiple avian functions in vineyard landscapes.…”
Section: Discussionsupporting
confidence: 56%
“…Organic farming benefits are thus enhanced by higher diversity and interspersion of semi-natural habitat patches in the landscape (Assandri et al, 2016;Rollan et al, 2019). Our results suggest that it is critical to also maintain a significant proportion of native vegetation within and between organic vineyards to integrate production and conservation efforts in sustainable viticulture (Froidevaux et al, 2017;Muñoz-Sáez et al, 2020). Management options mixing organic farming at the stand level and maintenance of semi-natural cover in the landscape are not only profitable to birds of conservation concern (Arlettaz et al, 2012;Brambilla, Gustin, et al, 2017), but also to the diversity of avian functions (Assandri et al, 2016;Barbaro et al, 2017;Lourenço et al, 2021).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations